The Adaptation of Almira Bastari’s Novel Home Sweet Loan into a Movie by Sabrina Rochelle Kalangie: A Study of Movie Adaptation - Radita Ainun Salsabila; Yuniseffendri (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the transformation of Almira Bastari’s novel Home Sweet Loan into a movie directed by Sabrina Rochelle Kalangie through a screen adaptation analysis. The study employs a descriptive qualitative approach using the techniques of reading, observing, and note-taking. The research data consists of excerpts from the novel and movie scenes that demonstrate these changes. Data analysis was performed by classifying the data into three forms of change: reduction, addition, and variation. The results of the study indicate that (1) reduction occurred in the plot, characterization, and conflict to accommodate the movie’s runtime; (2) additions were made to enhance the drama and visual storytelling; (3) variations were evident in modifications to the plot, characters, and setting tailored to cinematic needs. These findings indicate that the screen adaptation process not only transfers the story but also reconstructs its meaning to suit the medium of movie.